Error-based observation control of an image-based control loop for disturbance suppression in segmented lightweight large-scaled diffractive telescope (SLLDT). (September 2022) - Ruan, Yong; Xu, Tianrong; Liu, Yang; Xie, Zongliang; Ma, Haotong; Du, Junfeng; Yang, Tao; Tang, Tao; Yang, Hu; Peng, Zhenming
Highlights: An error-based observation control method is proposed for the SLLDT (segmented lightweight large-scaled diffractive telescope) to rejection disturbances. The disturbance suppression work is transferred from the output of the system to the closed-loop error of the system. By designing appropriate filters in the error-based observer, the low-frequency disturbance and large-amplitude narrowband disturbance in SLLDT are significantly suppressed. Abstract: Optical image systems are inevitably affected by disturbances, especially in a segmented lightweight large-scaled diffractive telescope (SLLDT), which is developed by our laboratory. The image-based control method is usually used to compensate disturbances caused by a long optical path in the SLLDT. However, a limited control bandwidth because of time delay degrades the disturbance suppression. An error-based observation control method is proposed for the SLLDT to rejection disturbances. Due to both the accurate disturbance model and additional sensors not required, this proposed method can relax the constraint between disturbance suppression and control stability. Simulations and experiments demonstrate that the proposed method has a significant improvement of sub-aperture image disturbance suppressions.